2020
DOI: 10.3390/app10103435
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Scaffolds for Skin Repair and Regeneration

Abstract: The skin is the largest organ in the body, fulfilling a variety of functions and acting as a barrier for internal organs against external insults. As for extensive or irreversible damage, skin autografts are often considered the gold standard, however inherent limitations highlight the need for alternative strategies. Engineering of human-compatible tissues is an interdisciplinary and active field of research, leading to the production of scaffolds and skin substitutes to guide repair and regeneration. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 99 publications
0
63
0
Order By: Relevance
“…Preserving rete ridges or creating rete ridge-mimicking patterns is a subject of great concern in tissue engineering strategies to promote rapid and robust DEJ formation. Studies of rete ridges have been conducted after application of autologous epithelial cells as composite grafts with decellularized dermis in patients and in animal models [65][66][67][68]. The slow deposition of basement membrane proteins and the lack of rete ridges or dermal papillae result in poor epidermal-dermal adhesion and functional outcomes for patients treated with cultured epithelial autograft [69][70][71][72].…”
Section: Expected Impact Of Rete Ridges In Epidermal Regenerationmentioning
confidence: 99%
“…Preserving rete ridges or creating rete ridge-mimicking patterns is a subject of great concern in tissue engineering strategies to promote rapid and robust DEJ formation. Studies of rete ridges have been conducted after application of autologous epithelial cells as composite grafts with decellularized dermis in patients and in animal models [65][66][67][68]. The slow deposition of basement membrane proteins and the lack of rete ridges or dermal papillae result in poor epidermal-dermal adhesion and functional outcomes for patients treated with cultured epithelial autograft [69][70][71][72].…”
Section: Expected Impact Of Rete Ridges In Epidermal Regenerationmentioning
confidence: 99%
“…The most common decellularization method involves the use of detergents such as SDS, which is considered an excellent agent for cell removal. When SDS was applied to human skin, porcine small intestinal submucosa, or fibroblast sheets, the efficiency of decellularization increased with concentration, although the overall ECM density, including the glycosaminoglycan content, decreased and the collagen fiber network was damaged [ 21 ]. In previous studies, SDS was applied at an average concentration of 0.5% w/v (range 0.1%–1%) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…When SDS was applied to human skin, porcine small intestinal submucosa, or fibroblast sheets, the efficiency of decellularization increased with concentration, although the overall ECM density, including the glycosaminoglycan content, decreased and the collagen fiber network was damaged [ 21 ]. In previous studies, SDS was applied at an average concentration of 0.5% w/v (range 0.1%–1%) [ 21 ]. H-ADM-low was produced using SDS at 0.25%, which is half of the average concentration, and HE staining showed that the matrix was completely decellularized, i.e., there were no residual cell debris or other immunogenic components of the native skin.…”
Section: Discussionmentioning
confidence: 99%
“…The commercial landscape of dermal allografts is complex and varied due to the many different processing strategies employed to retain or omit layers of the dermis, basement membrane, and epidermis. Therefore, skin tissue can be processed for many applications such as burns, reconstructive surgery, chronic or acute wounds, or soft tissue repair [ 47 , 48 ]. This review has highlighted an application of dermal allografts for sports medicine in tendon repair.…”
Section: Decellularized Tissuementioning
confidence: 99%